The Predictive Value of Preendoscopic Risk Scores to Predict Adverse Outcomes in Emergency Department Patients With Upper Gastrointestinal Bleeding: A Systematic Review. (1st November 2016) - Ramaekers, Rosa; Mukarram, Muhammad; Smith, Christine A. M.; Thiruganasambandamoorthy, Venkatesh
Abstract: Objectives: Risk stratification of emergency department (ED) patients with upper gastrointestinal bleeding (UGIB) using preendoscopic risk scores can aid ED physicians in disposition decision‐making. We conducted a systematic review to assess the predictive value of preendoscopic risk scores for 30‐day serious adverse events. Methods: We searched MEDLINE, PubMed, Embase, and the Cochrane Database of Systematic Reviews from inception to March 2015. We included studies involving adult ED UGIB patients evaluating preendoscopic risk scores and excluded reviews, case reports, and animal studies. The composite outcome included 30‐day mortality, recurrent bleeding, and need for intervention. In two phases (screening and full review), two reviewers independently screened articles for inclusion and extracted patient‐level data. The consensus data were used for analysis. We reported sensitivity, specificity, positive and negative predictive value, and positive and negative likelihood ratios with 95% confidence intervals. Results: We identified 3, 173 articles, of which 16 were included: three studied Glasgow Blatchford score (GBS); one studied clinical Rockall score (cRockall); two studied AIMS65; six compared GBS and cRockall; three compared GBS, a modification of the GBS, and cRockall; and one compared the GBS and AIMS65. Overall, the sensitivity and specificity of the GBS were 0.98 and 0.16, respectively; for the cRockall they were 0.93 and 0.24, respectively; and for the AIMS65 they were 0.79 and 0.61, respectively. The GBS with a cutoff point of 0 had a sensitivity of 0.99 and a specificity of 0.08. Conclusion: The GBS with a cutoff point of 0 was superior over other cutoff points and risk scores for identifying low‐risk patients but had a very low specificity. None of the risk scores identified by our systematic review were robust and, hence, cannot be recommended for use in clinical practice. Future prospective studies are needed to develop robust new scores for use in ED patients with UGIB.